Extensively drug-resistant pseudomonas aeruginosa ST309 harboring tandem Guiana extended spectrum β-lactamase enzymes: a newly emerging threat in the united states (2019)
Treatment of serious infections due to multidrug-resistant (MDR) Pseudomonas aeruginosa remains a challenge, despite the introduction of novel therapeutics. In this study, we report 2 extensively drug-resistant clinical isolates of sequence type (ST) 309 P aeruginosa resistant to all β-lactams, including the novel combinations ceftolozane/tazobactam, ceftazidime/avibactam, and meropenem/vaborbactam. Isolates were sequenced using both short-read (Illumina) and long-read technology to identify resistance determinants, polymorphisms (compared with P aeruginosa PAO1), and reconstruct a phylogenetic tree. A pair of β-lactamases, Guiana extended spectrum β-lactamase (GES)-19 and GES-26, were cloned and expressed in a laboratory strain of Escherichia coli to examine their relative impact on resistance. Using cell lysates from E coli expressing the GES genes individually and in tandem, we determined relative rates of hydrolysis for nitrocefin and ceftazidime. Two ST309 P aeruginosa clinical isolates were found to harbor the extended spectrum β-lactamases GES-19 and GES-26 clustered in tandem on a chromosomal class 1 integron. The presence of both enzymes in E coli was associated with significantly elevated minimum inhibitory concentrations to aztreonam, cefepime, meropenem, ceftazidime/avibactam, and ceftolozane/tazobactam, compared with those expressed individually. The combination of ceftazidime/avibactam plus aztreonam was active in vitro and used to achieve cure in one patient. Phylogenetic analysis revealed ST309 P aeruginosa are closely related to MDR strains from Mexico also carrying tandem GES. The presence of tandem GES-19 and GES-26 is associated with resistance to all β-lactams, including ceftolozane/tazobactam. Phylogenetic analysis suggests that ST309 P aeruginosa may be an emerging threat in the United States.